2013
DOI: 10.1021/om4005302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Added Salt on Ring-Closing Metathesis Catalyzed by a Water-Soluble Hoveyda–Grubbs Type Complex To Form N-Containing Heterocycles in Aqueous Media

Abstract: The efficiency of ring-closing metathesis catalyzed by a Hoveyda–Grubbs type catalyst in water can be enhanced by addition of a chloride salt under neutral conditions. UV–vis spectroscopic study showed that a characteristic band of the catalyst around 380 nm remained over 16 h in the presence of KCl, whereas the band distinctly decreased in the absence of KCl. The disappearance of the band is ascribed to a displacement of a chloride ligand by a water molecule or a hydroxide anion. The spectral changes can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
(22 reference statements)
0
40
0
Order By: Relevance
“…Al ikely explanation for this observation is the smalli ncreasei ns olubility of the catalyst compared to catalyst C2,w hichc ontains partly hydrophobic triflate anions. With catalyst C1,f urther attempts to increaset he self-metathesis yields were based on observations made by Davis et al [54] and Hirota et al, [62] in which addition of ac hloride salt prevented nonproductive chelation/deactivation of the catalysts. In the present case, addition of magnesium chloride( 100 mm)i mproved the self-metathesis conversions only marginally in the reactions with the functionalized carbohydrates.…”
Section: Resultsmentioning
confidence: 99%
“…Al ikely explanation for this observation is the smalli ncreasei ns olubility of the catalyst compared to catalyst C2,w hichc ontains partly hydrophobic triflate anions. With catalyst C1,f urther attempts to increaset he self-metathesis yields were based on observations made by Davis et al [54] and Hirota et al, [62] in which addition of ac hloride salt prevented nonproductive chelation/deactivation of the catalysts. In the present case, addition of magnesium chloride( 100 mm)i mproved the self-metathesis conversions only marginally in the reactions with the functionalized carbohydrates.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the particle size was smaller with ionic stabilization (CTAC and CTAB) compared to Triton X‐100. With SDS, the polymerization did not occur at all, likely due to the sulfate group of SDS and the catalyst forming inactive species . We also found that dodecane was an effective miniemulsion costabilizer at low concentration (0.5 wt% based on monomer).…”
Section: Summary Of Experimental Results: Experiment Molar Ratio Monmentioning
confidence: 72%
“…Under slightly acidic conditions (pH 5.8), full conversion was observed with the metal complex coupled to the fully unfolded protein ( Table 2 , entries 2–4) [ 59 60 ]. This effect was attributed to the pH and was investigated in detail [ 61 ].…”
Section: Reviewmentioning
confidence: 99%